2018
DOI: 10.1152/ajpheart.00152.2017
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet decomposition analysis is a clinically relevant strategy to evaluate cerebrovascular buffering of blood pressure after spinal cord injury

Abstract: The capacity of the cerebrovasculature to buffer changes in blood pressure (BP) is crucial to prevent stroke, the incidence of which is three- to fourfold elevated after spinal cord injury (SCI). Disruption of descending sympathetic pathways within the spinal cord due to cervical SCI may result in impaired cerebrovascular buffering. Only linear analyses of cerebrovascular buffering of BP, such as transfer function, have been used in SCI research. This approach does not account for inherent nonlinearity and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…As a result of ANS impairment, cardiovascular dysfunction is common and takes the form of blood pressure instability, which includes persistent hypotension, orthostatic hypotension, and autonomic dysreflexia. These blood pressure disorders have been implicated in an increased prevalence of cerebrovascular compromise (Saleem et al, 2018 ), cognitive deficits (Wecht et al, 2018 ), and stroke (Wu et al, 2012 ), which are independent of symptom reporting in the majority of individuals with SCI. It is thought that an additional consequence of ANS impairment is immune system dysfunction (Schwab et al, 2014 ; Herman and Bloom, 2018 ), which promotes systemic inflammation, and may also play a role in long-term cardiovascular morbidity and mortality following SCI.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of ANS impairment, cardiovascular dysfunction is common and takes the form of blood pressure instability, which includes persistent hypotension, orthostatic hypotension, and autonomic dysreflexia. These blood pressure disorders have been implicated in an increased prevalence of cerebrovascular compromise (Saleem et al, 2018 ), cognitive deficits (Wecht et al, 2018 ), and stroke (Wu et al, 2012 ), which are independent of symptom reporting in the majority of individuals with SCI. It is thought that an additional consequence of ANS impairment is immune system dysfunction (Schwab et al, 2014 ; Herman and Bloom, 2018 ), which promotes systemic inflammation, and may also play a role in long-term cardiovascular morbidity and mortality following SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Fergus et al ( 2018 ) which examined only FHR dynamics, the present study investigated nonlinear and nonstationary UC-FHR couplings using the multivariate extension of EMD. For this, scale-matched empirically derived modes of FHR and UC were examined to develop a set of unique features which have previously been applied to quantify various physiological systems (Saleem et al, 2016 , 2018 ; Bhattacharyya and Pachori, 2017 ). We observed that AdaBoost classifier performs on-par with the best accuracy i.e., 91.8% sensitivity, 95.5% specificity, 98% AUC and 5% MSE.…”
Section: Discussionmentioning
confidence: 99%
“…Phase synchronization index (PSI) between instantaneous phases of m th IMFs for FHR (ϕγmtextF(t)) and UC (ϕγmtextU(t)) is calculated as (Saleem et al, 2016, 2018)…”
Section: Feature Extractionmentioning
confidence: 99%
“…As a result, there is a significant disparity between the prevalence of chronic blood pressure instability in SCI and its treatment (Zhu et al, 2013). There is also mounting evidence that, even when asymptomatic, chronic blood pressure instability can impair the ability of the cerebral vasculature to buffer blood pressure (Saleem et al, 2018) and dramatically increase the risk of stroke (Eigenbrodt et al, 2000;Wu et al, 2012), increase arterial stiffness (Currie et al, 2019) and cause cognitive impairment (Jegede et al, 2010;Sachdeva et al, 2019;Wecht & Bauman, 2013;Wecht et al, 2012), leading to significant cardiovascular morbidity and mortality. Therefore, a valid method to assess and quantify the degree of cardiovascular autonomic impairment is needed for the goal of reducing cardiovascular morbidity and mortality and improving health-related quality of life after SCI.…”
Section: Prevalence Of Orthostatic Hypotension By Level and Severitmentioning
confidence: 99%